Association between use of systematic reviews and national policy recommendations on screening newborn babies for rare diseases: systematic review and meta-analysis. (9th May 2018) - Taylor-Phillips, Sian; Stinton, Chris; Ferrante di Ruffano, Lavinia; Seedat, Farah; Clarke, Aileen; Deeks, Jonathan J
Abstract: Objective: To understand whether international differences in recommendations of whether to screen for rare diseases using the newborn blood spot test might in part be explained by use of systematic review methods. Design: Systematic review and meta-analysis. Data sources: Website searches of 26 national screening organisations. Eligibility criteria for study selection: Journal articles, papers, legal documents, presentations, conference abstracts, or reports relating to a national recommendation on whether to screen for any condition using the newborn blood spot test, with no restrictions on date or language. Data extraction: Two reviewers independently assessed whether the recommendation for or against screening included systematic reviews, and data on test accuracy, benefits of early detection, and potential harms of overdiagnosis. Analysis: The odds of recommending screening according to the use of systematic review methods was estimated across conditions using meta-analysis. Results: 93 reports were included that assessed 104 conditions across 14 countries, totalling 276 recommendations (units of analysis). Screening was favoured in 159 (58%) recommendations, not favoured in 98 (36%), and not recommended either way in 19 (7%). Only 60 (22%) of the recommendations included a systematic review. Use of a systematic review was associated with a reduced probability of screening being recommended (23/60 (38%) v 136/216 (63%), odds ratio 0.17, 95% confidence interval 0.07 to 0.43). Of the recommendations, evidence for test accuracy, benefits of early detection, and overdiagnosis was not considered in 115 (42%), 83 (30%), and 211 (76%), respectively. Conclusions: Using systematic review methods is associated with a reduced probability of screening being recommended. Many national policy reviews of screening for rare conditions using the newborn blood spot test do not assess the evidence on the key benefits and harms of screening.